2007
DOI: 10.1149/1.2729277
|View full text |Cite
|
Sign up to set email alerts
|

Fuel Impurity Tolerance of Solid Oxide Fuel Cells

Abstract: While SOFCs are the most flexible fuel cells with respect to fuel selection, fuel impurities in practical SOFC fuels can cause degradation of electrodes and thus electrochemical performance. The understanding of fuel impurity poisoning and the increase in tolerance are therefore of technological relevance for SOFC commercialization. Along with thermochemical calculations on the stability of typical fuel impurities under SOFC operational conditions, fuel impurity poisoning of SOFCs is analyzed by using various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
46
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 3 publications
0
46
0
Order By: Relevance
“…Various degradation mechanisms, however, may appear, such as impurity poisoning, e.g. by H 2 S, affecting the anode performance (1). On the cathode side, chromium can evaporate from metallic components to cathode, leading to cathode degradation (2).…”
Section: Introductionmentioning
confidence: 99%
“…Various degradation mechanisms, however, may appear, such as impurity poisoning, e.g. by H 2 S, affecting the anode performance (1). On the cathode side, chromium can evaporate from metallic components to cathode, leading to cathode degradation (2).…”
Section: Introductionmentioning
confidence: 99%
“…The effect of chlorine gas in conjunction with SOFC was analysed in several articles. Sasaki et al (2007) published experiments which show that fuel gas containing 5 ppmv of Cl does not cause a cell degradation or voltage drop in the SOFC. Błesznowski et al (2013) investigated the effect of HCl-contaminated fuel gas and concluded that at 10 ppmv a recoverable voltage drop is identified.…”
Section: Introductionmentioning
confidence: 99%
“…Poisoning by sulfur compounds occurs generally in the following way: the cell voltage decreases rapidly after adding impurity to fuel gas followed by a quasi‐steady state with a constant cell voltage . In order to use biogas as fuel for a SOFC, several of its components have to be reduced to a certain degree.…”
Section: Introductionmentioning
confidence: 99%